Analisis Manfaat (Maslahat) BMT Ditinjau Dari Persepsi Pengusaha Mikro - Mujtahidah, Hikmah (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
Welfare is an aim of every human life. Usaha Mikro Kecil Menengah (UMKM) is one effort to achieve the aim. However, in practice, there are many difficulties faced by the entrepreneurs of UMKM, including in terms of capital/material. BMT is a financial institution based on cooperative with the principle of cooperation. One goal of BMT is to empower small entrepreneurs to grow the bussiness up and nd be able to compete ith the others. This research is the field reserch that ill analyze the benefits of BMT from the micro entrepreneurs??? perspective in Gresik, which involves several informants as primary sources. This study concludes that the financing done by BMT Nurul Jannah Petrokimia has benefits to micro entrepreneurs, such as asset increase, sales / earnings increase, income increase, and stability of the business undertaken. Other benefits are business assistance programs and empowerment of religious activities.